Image Fusion using Principal Component Analysis and Discrete Wavelet Transform - Induja, P; Chellam, G. Heren (International Journal of Computer Sciences and Engineering, 2025)
Image fusion is the process of combining two or more images to produce one single fused image. The Fusion process was worked on collecting all the relevant information from the input images and returns a single image. This single image has more informative and accurate than the other input images, and it is consist of all the necessary information. The final fused image is formed by combining many input images into one single image. This paper presents PCA and wavelet transform based Image Fusion